Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/nu15071754
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ingesting Food Containing Heat-Killed Lactococcus lactis Strain Plasma on Fatigue and Immune-Related Indices after High Training Load: A Randomized, Double-Blind, Placebo-Controlled, and Parallel-Group Study

Abstract: Lactococcus lactis strain Plasma (LC-Plasma) is a unique lactic acid bacterium that activates plasmacytoid dendritic cells (pDCs). We evaluated the effect of LC-Plasma on fatigue indices and dendritic cells activity in athletes after 14 days’ continuous exercise load. Thirty-seven participants were divided into two groups and consumed placebo (PL) or LC-Plasma capsules (containing 100 billion cells) daily for 14 days. Maturation markers on dendritic cells, blood parameters, physiological indices, and fatigue-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Following this, Komano and investigators [ 65 ] conducted another investigation in which they divided 37 participants into two groups who took either a placebo or capsules containing 1.0 × 10 11 cells of Lactococcus lactis JCM 5805 for 14 days while continually exercising. Blood samples were collected to evaluate changes in immune activity (CD86 from plasmacytoid dendritic cells, pDCs), and fatigue was assessed before, throughout, and following the supplementation regimen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following this, Komano and investigators [ 65 ] conducted another investigation in which they divided 37 participants into two groups who took either a placebo or capsules containing 1.0 × 10 11 cells of Lactococcus lactis JCM 5805 for 14 days while continually exercising. Blood samples were collected to evaluate changes in immune activity (CD86 from plasmacytoid dendritic cells, pDCs), and fatigue was assessed before, throughout, and following the supplementation regimen.…”
Section: Discussionmentioning
confidence: 99%
“…The Sawada et al [ 39 ], Komano et al [ 58 , 65 ], and Sashirara [ 64 ] studies all utilized cohorts of competitive athletes and demonstrated the ability of postbiotics to help offset fatigue, illness, infection, and negative changes in mood and depression. Collectively, these results are particularly valuable as the current postbiotic and sports literature has yet to fully examine the ability of postbiotics to support immune system health across an entire training year.…”
Section: Discussionmentioning
confidence: 99%